Nurses’ preparedness for disaster response in rural and urban primary healthcare settings in Tanzania - Kahabi Isangula; Mary Lyimo; Yudas Ndungile; Elisha Robert (James Cook University, 2023)
Introduction: Nurses are often on the frontline of disaster management, providing care to patients with emerging physical, mental, and emotional turbulence, and acting as educators for health promotion and disaster prevention in both rural and urban contexts. However, the literature suggests that nurses are inadequately prepared for disaster response. This study examined preparedness for disaster response among nurses in rural and urban primary healthcare settings in Tanzania. Methods: This qualitative descriptive study involved purposefully selected qualified nurses and nurse administrators working in rural (n=20) and urban (n=11) primary healthcare facilities in Tanzania. Telephone-based interviews were conducted to gather data that were then analyzed thematically. Results: Five themes emerged from the analysis: previous experiences, technical capacity, current strategies, challenges, and overall preparedness. Previous experiences included personally caring for victims, working in disaster response teams, working in administrative roles during disasters, and conducting community sensitization. Most nurses in rural contexts had not received training on disaster response and relied on past experience, knowledge from nursing school, observing peers, and knowledge from the internet and movies. Current strategies for disaster response included response teams (although these were considered 'weak'), ensuring the availability of equipment and supplies, and infrastructure for victim management. Challenges in disaster response included inadequate resources, understaffing, lack of expertise at primary healthcare facilities, nurses tasked with multiple responsibilities, inadequate technical capacity, fears of infection, poor interpersonal relationships, inadequate community knowledge, poor reporting systems, delayed healthcare seeking, long distances to facilities, and poor road infrastructure. These challenges were more pronounced in rural settings. Most nurses felt they were well prepared to respond to disasters, although this appeared to be rooted in a willingness to provide care rather than having adequate knowledge, skills, and resources for disaster response. Suggestions for better preparing nurses for disaster response included training, increasing essential equipment and medical supplies, increasing the nursing workforce, improving reporting systems, disseminating local guidelines, strengthening disaster response teams, and improving the nursing training curricula to cover disaster management. Conclusion: A range of institutional, individual, and community challenges affect nurses' preparedness for disaster response in rural and urban primary healthcare settings. Addressing these challenges requires multiple strategies that extend beyond the capacity building of nurses to strengthen health system disaster preparedness in general, prioritizing rural contexts.